PREDIKSI TINGKAT KEBANGKRUTAN SEBELUM DAN SELAMA PANDEMI COVID-19 MENGGUNAKAN METODE ALTMAN Z-SCORE - R. Apria Susiana; Lilik Puwanti (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2021)
The purpose of this study was to examine differences in the level of bankruptcy in transportation companies listed on the IDX before and during the Covid-19 pandemic. This type of research is quantitative using purposive sampling technique which produces 57 samples. The data collection technique used a study of documentation obtained from the IDX's official website, namely www.idx.co.id. Data analysis used SPSS version 21 software. The results showed that the company that had the highest bankruptcy rate in the 2018-2020 period was BLTA due to a decrease in all financial ratios, while the company that had the lowest bankruptcy rate was SAPX because the company managed to increase its solvency and profitability ratios. The results of other studies are that there is no difference in the level of bankruptcy before and during the Covid-19 pandemic. This means that the company has a bankruptcy rate that is not much different from before and during the Covid-19 pandemic because the company is able to adapt by implementing strategies that are in accordance with the conditions of the Covid-19 pandemic.